Webbed Integrative Approach in Designing Writing Instruction for Indonesian Elementary Class in the Digital Era - Asdar Asdar; Muhammad Asdam; Andi Hamsiah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Traditional teaching materials often rely heavily on textbooks and mid-range content, lacking integration with thematic learning models. This study explored the use of teaching materials based on the webbed-type integrated learning model for the theme of living things, in contrast to the traditional use of mid-range materials and textbooks. The objective was to evaluate the effectiveness of these integrated materials on students' essay-writing skills. A quantitative experimental design was employed, involving a sample of 22 students selected through total sampling. The findings revealed that the webbed learning model significantly improved students' essay writing abilities, as evidenced by higher post-test scores compared to pre-test scores. Consequently, it can be concluded that webbed-type integrated teaching materials positively impact thematic lessons on the theme of living things and serve as a valuable resource for educators in enhancing the thematic learning process.